SPATIAL ANALYSIS OF THE “ONE MILLION HOUSES” PROGRAM IN THE SETIF URBAN AGGLOMERATION WITHIN MASTER PLAN OF LAND USE AND URBANISM: POLYMORPHISM AND SPATIAL DISTRIBUTION (ALGERIA) - Djaadjou Mahfoud,; Benghadbane Foued, (International Journal of Innovative Technologies in Social Science, 2025)
Housing supply is a crucial issue in any country's planning strategies. It represents one of the most sensitive social sectors, which the State strives to develop and make accessible to all segments of society. Guaranteeing decent housing is therefore one of the fundamental priorities that enable every individual to lead a stable life and aspire to start a family in peaceful conditions.Given the growing importance of the housing sector, this study sets out to provide a detailed picture of the reality of housing supply, in its various forms and at different spatial levels. It uses the urban agglomeration of Sétif, located in the Algeria's Eastern High Plateaus, as the basis for its analysis, in order to identify the types of housing available and assess their spatial distribution.To achieve the research objectives, we adopted a descriptive-analytical approach to identify the actual mechanisms and planning logics used in the distribution of housing projects and their forms within the framework of the “One million houses” programme across the intervention zone of the Sétif Inter-communal Development Master Plan. The article also used an analytical-comparative approach to highlight the extent of spatial balance in the location of housing projects in the various communes of the urban agglomeration of Sétif.The study revealed a significant disparity in the distribution of housing projects linked to the one million houses programme in the urban area of Sétif. This disparity is mainly explained by the differences in the size of the beneficiaries of these projects, themselves influenced by the unequal financial capacities of the communes. In addition, the type of housing produced varies according to the formats imposed by the five-year plans adopted by the Algerian government, which have played a decisive role in this distribution.